2021
DOI: 10.4103/ijciis.ijciis_98_20
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the vasoactive-inotropic score in predicting pediatric septic shock mortality

Abstract: Introduction: Mortality in pediatric septic shock remains very high. Vasoactive-inotropic score (VIS) is widely used to predict prognosis in patients with heart disease. It is a simple method that was initially used as a predictor of morbidity and mortality in postoperative patients with congenital heart diseases. Previous reports showed that high VIS score was associated with high mortality in pediatric sepsis. However, its discriminative value remains unclear. We aim to explore the discriminativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In a study by Pudjiadi et al, VIS > 11 was a good predictor of mortality in children with septic shock. 24 In a study by Fatimah et al reported that the cut-off value of the ROC curve of VIS concerning mortality was 6 with a sensitivity and specificity of 82.1% and 64.5%, respectively. 25 Previous studies on VIS in children have only associated VIS with cardiac surgery in pediatrics.…”
Section: Dovepressmentioning
confidence: 97%
“…In a study by Pudjiadi et al, VIS > 11 was a good predictor of mortality in children with septic shock. 24 In a study by Fatimah et al reported that the cut-off value of the ROC curve of VIS concerning mortality was 6 with a sensitivity and specificity of 82.1% and 64.5%, respectively. 25 Previous studies on VIS in children have only associated VIS with cardiac surgery in pediatrics.…”
Section: Dovepressmentioning
confidence: 97%
“…The VIS is easy to measure, and the results may be calculated instantaneously at the patient’s bedside. Currently, it is used to assess the severity of cardiac malfunction and to estimate the degree of cardiovascular drug support in infants after cardiac surgery [ 13 ]. The cause of CDH-related death is respiratory and circulatory failure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals could receive inotropic support comprising epinephrine, norepinephrine, milrinone and vasopressin if necessary in order to maintain the mean arterial pressure above 60 mmHg and the cardiac index above 2 L/min per m 2 . The decision to provide inotropic support was based on the animal's vasoactive-inotropic score ( 10 ). Weaning was considered a failure if hemodynamics did not stabilize within 2 h on cardiopulmonary bypass.…”
Section: Methodsmentioning
confidence: 99%